Perancangan Logika Fuzzy Untuk Sistem Pengendali Kelembaban Tanah dan Suhu Tanaman - Nasron, Nasron; Suroso, Suroso; Putri, Astriana Rahma (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Soil moisture and temperature are parameters needed by plants in terms of plant growth. In determining soil moisture and temperature according to plants, a control system is needed. This control system uses the Raspberry Pi as an input data processor to output. This control system is designed using fuzzy logic as a decision-making method to maintain soil moisture and temperature that is good for plants. Fuzzy logic is one of the decision support systems that is suitable to be applied to the control system. Fuzzy logic consists of fuzzyfication, formation of fuzzy rules and defuzification. This fuzzy logic uses two inputs and two outputs. The two inputs are soil moisture level and temperature degree. The desired output is the time needed to maintain soil moisture and temperature to keep it in accordance with the needs of the plant